Temperature Dependent Electrical Properties and Catalytic Activities of La2O3–CO2–H2O Phase System. (28th December 2009) - Bakiz, Bahcine; Guinneton, Frédéric; Arab, Madjid; Villain, Sylvie; Benlhachemi, Abdeljalil; Gavarri, Jean Raymond
Abstract : We present a study of electrical properties and catalytic activities of materials belonging to the hydrated carbonated systemLa 2 O 3 – CO 2 – H 2 O . The polycrystalline hydroxycarbonate, dioxycarbonate, and oxide are prepared via a coprecipitation route followed by heat treatment. The electrical conduction of the phases obtained by thermal decomposition fromLaOHCO 3, H 2 O is analyzed by electrical impedance spectroscopy, from25 ° C to950 ° C, under air. The catalytic properties ofLaOHCO 3, La 2 O 2 CO 3 andLa 2 O 3 polycrystalline phases are studied by FTIR spectroscopy, in presence of gas mixtures CO-air andCH 4 -air, at temperatures ranging between100 ° C to525 ° C . The three materials behave differently in presence of CO orCH 4 gases.